2013
DOI: 10.1016/j.solmat.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of capacitance spectroscopy signals of CIGS solar cells to effects of non-ohmic contacts

Abstract: We report evidence for the idendification of the capacitance transients detected at room temperature for thin-film photovoltaic cells with CIGS absorbers as an additional non-ohmic contact in the structure with a time constant larger than that of the solar cell pn-jucntion. The N1 signal was recently interpreted as a back contact barrier for which the RC-like time constant is smaller than the time constant of the junction. In this work we unite these experimental observations in one model. Since for a Mo/CIGS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Lauwaert et al showed that DLTS signals recorded for different pulse directions are not compatible with standard models of carrier capture and emission by defect states in the device. Instead, R‐C‐ like non‐ideal contacts or interlayers in series with the main junction were shown to result in capacitance steps and DLTS peaks which could explain the N1 signature . With the main junction located at the front CIGS/buffer interface in the device, the R‐C ‐like barrier or counter‐diode in series with the main junction has been attributed to the back contact in these studies.…”
Section: Introductionmentioning
confidence: 84%
“…Lauwaert et al showed that DLTS signals recorded for different pulse directions are not compatible with standard models of carrier capture and emission by defect states in the device. Instead, R‐C‐ like non‐ideal contacts or interlayers in series with the main junction were shown to result in capacitance steps and DLTS peaks which could explain the N1 signature . With the main junction located at the front CIGS/buffer interface in the device, the R‐C ‐like barrier or counter‐diode in series with the main junction has been attributed to the back contact in these studies.…”
Section: Introductionmentioning
confidence: 84%
“…Primarily, it has been attributed to a defect, although conflicting evidence exists concerning where these defects are located within the device [9,11,12]. This standard interpretation was recently challenged by an increasing number of publications which suggest alternative explanations for the N1 level, mostly linked to the transport characteristics of the solar-cell absorber [13,14] or to a transport barrier [7,[15][16][17][18][19][20][21] within the device.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its high absorption coefficient, appropriate band gap and outstanding electro-optical properties [1][2][3]. CIGSbased solar cells with x = 0.3 which corresponds to a band-gap energy range of 1.1-1.2 eV yields the best efficiency both in laboratory and commercial solar cells [3].…”
Section: Introductionmentioning
confidence: 99%